Atomic and electronic band structures of Ti-doped Al2O3 grain boundaries. (December 2020) - Yang, Chuchu; Feng, Bin; Wei, Jiake; Tochigi, Eita; Ishihara, Saki; Shibata, Naoya; Ikuhara, Yuichi
Abstract: Doping is one of the most popular strategies to modify the properties of polycrystalline materials, because the dopants prefer to segregate at the grain boundaries (GBs) and influence the structural and electronic properties of the materials. Understanding how dopants segregate at GBs and how they affect the resultant GB properties are essential. Here, we experimentally characterized the atomic structures and the electronic band structures of Ti-doped Σ7 { 4 5 ¯ 10 } and Σ7 { 2 3 ¯ 10 } GBs in α-Al2 O3 by atomic resolution scanning transmission electron microscopy (STEM), energy-dispersive X-ray spectroscopy (EDXS) and valence electron energy-loss spectroscopy (EELS). It was found that Ti preferentially segregated at specific atom sites driven by ionic size mismatch between Ti 3+ and Al 3+, which leads to structural transformations in both GBs. Direct valence EELS measurement revealed the segregation of Ti 3+ ions introduces impurity band within the bandgap in Al2 O3 GBs. These results provide an in-depth understanding of the local atomic and electronic band structures for Ti-doped GBs. Graphical abstract: Image, graphical abstract